2014
DOI: 10.1007/s00103-013-1927-7
|View full text |Cite
|
Sign up to set email alerts
|

Nosokomiale Infektionen, systemischer Antibiotikaeinsatz und multiresistente Erreger bei Bewohnern von Altenpflegeheimen

Abstract: The HAIs and antibiotic use were comparable to the German HALT data from 2010. Compared to other German studies there is a steadily increasing MRSA problem in German LTCFs. High and increasing ESBL rates have been detected in German LTCFs. Further studies are needed to confirm this trend, preferably encompassing molecular methods to study epidemiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 41 publications
1
10
0
4
Order By: Relevance
“…More recent studies reported MRSA prevalence of between 2.3 and 9.2% [2126]. In other European countries, lower prevalence of 0% and 0.3% was reported in Sweden [27] and the Netherlands [28] respectively, but there was also a higher MRSA prevalence of 12.2% in Belgium [29], 7.2% in Luxembourg [30] and 10.6% in Spain [31].…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies reported MRSA prevalence of between 2.3 and 9.2% [2126]. In other European countries, lower prevalence of 0% and 0.3% was reported in Sweden [27] and the Netherlands [28] respectively, but there was also a higher MRSA prevalence of 12.2% in Belgium [29], 7.2% in Luxembourg [30] and 10.6% in Spain [31].…”
Section: Discussionmentioning
confidence: 99%
“…4 Antibiotikagruppen (3MRGN, 4MRGN) in Kliniken in Deutschland liegen kaum vordie verfügbaren Daten zum Anteil von multiresistenten Isolaten in Deutschland resultieren im Wesentlichen aus Surveillance-Untersuchungen [5,16]. Deutlich höhere MRSA Prävalenzen sind aus Altenpflegeheimen beschrieben [17,18]. Das MRE-Netz Rhein-Main hat sich zum Ziel gesetzt, die Rehabilitation von Patienten mit MRSA und anderen multiresistenten Erregern zu verbessern [19].…”
unclassified
“…Der Vergleich mit anderen Untersuchungen im Rhein-Main-Gebiet in den letzten Jahren zeigt, dass die MRSAPrävalenz der Patienten der ambulanten Pflegedienste mit 3,7 % deutlich unter der MRSA-Prävalenz bei Altenpflegeheimbewohnern (6,5 % resp. 9,2 %) [14,15], aber über der MRSA-Prävalenz bei ambulanten Dialysepatienten (2,1 %) [16] und Rehabilitationspatienten (0,7 %, resp. 1,8 %) [17,18] liegt.…”
Section: Discussionunclassified
“…erhoben und publiziert [11,12]. Darüber hinaus liegen verschiedene Untersuchungen zur MREPrävalenz bei Altenpflegeheimbewohnern vor (Literatur in [22]) [14,15]. Im Gegensatz dazu gibt es praktisch keine Erhebungen in der ambulanten Pflege zu den Patientencharakteristika und nur wenige Untersuchungen zur MRSAPrävalenz [8][9][10] …”
Section: Introductionunclassified